2022
DOI: 10.3390/biom12111587
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Tuning of mTORC1-ULK1-PP2A Regulatory Triangle Is Crucial for Robust Autophagic Response upon Cellular Stress

Abstract: Autophagy-dependent cellular survival is tightly regulated by both kinases and phosphatases. While mTORC1 inhibits autophagy by phosphorylating ULK1, PP2A is able to remove this phosphate group from ULK1 and promotes the key inducer of autophagosome formation. However, ULK1 inhibits mTORC1, mTORC1 is able to down-regulate PP2A. In addition, the active ULK1 promotes PP2A via phosphorylation. We claim that these double-negative (mTORC1 –| PP2A –| mTORC1, mTORC1 –| ULK1 –| mTORC1) and positive (ULK1 -> PP2A -&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…As the stress increases in the cell, an unstable steady state is formed surrounded with a stable limit cycle (see unfilled circle and grey trajectories in Figure 2B). Computer simulations also confirm that although mTOR is knocked out of the network (directly or indirectly via AMPK activation), oscillations of autophagy initiation are observed through the delayed negative feedback loop of AMPK -> "regulator" -> ULK1 -| AMPK (Figure 2C), which is consistent with our previous experimental results [33,34]. We claim that, in this way, the system might have an opportunity to release energy and utilise the building blocks produced from more complex biological elements via autophagy.…”
Section: Time-delayed Negative Feedback Loop Results In Periodic Acti...supporting
confidence: 90%
See 2 more Smart Citations
“…As the stress increases in the cell, an unstable steady state is formed surrounded with a stable limit cycle (see unfilled circle and grey trajectories in Figure 2B). Computer simulations also confirm that although mTOR is knocked out of the network (directly or indirectly via AMPK activation), oscillations of autophagy initiation are observed through the delayed negative feedback loop of AMPK -> "regulator" -> ULK1 -| AMPK (Figure 2C), which is consistent with our previous experimental results [33,34]. We claim that, in this way, the system might have an opportunity to release energy and utilise the building blocks produced from more complex biological elements via autophagy.…”
Section: Time-delayed Negative Feedback Loop Results In Periodic Acti...supporting
confidence: 90%
“…Our goal here is to explain the dynamical features of both negative and doublenegative feedback loops of ULK1-controlled autophagy induction. By using systems biology methods, we recently confirmed that autophagy induction has an oscillatory characteristic upon various cellular stress events [33][34][35]. We proved both experimentally and theoretically that nutrient deprivation or mTOR (here, mTOR refers to mTORC1) inhibition via rapamycin treatment resulted in the periodic repeat of ULK1 activation and inactivation, and created an oscillatory characteristic of autophagy [33].…”
Section: Time-delayed Negative Feedback Loop Results In Periodic Acti...mentioning
confidence: 70%
See 1 more Smart Citation
“…Previously, our group has made some mathematical models to analyze the ER stress-response mechanism [ 17 , 18 ], focusing on the crosstalk between autophagy and apoptosis [ 19 , 20 ] and the autophagy-dependent survival mechanism under various types of cellular stress [ 21 , 22 , 23 , 24 ]. We have found that autophagy can be periodically activated due to the delayed negative feedback loop between AMPK and ULK1 [ 22 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have found that autophagy can be periodically activated due to the delayed negative feedback loop between AMPK and ULK1 [ 22 , 25 ]. Furthermore, we have claimed that a robust autophagy response mechanism requires double-negative and positive feedback loops in the system [ 24 ]. We have previously confirmed that the mutual antagonism between AUTA effector (autophagy effector) and APOA effector (apoptosis effector) guarantees that autophagy and apoptosis cannot be active at the same time with respect to ER stress [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%